Faktor-faktor yang Memengaruhi Kualitas Laporan Keuangan Desa Kecamatan Tapos - Adam, Zarhan Febry; Rusmanah, Enok; Situmorang, Monang (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The quality of financial reports is a critical goal for public sector organizations, representing their accountability for the authority and resources entrusted to them. Several key factors influence the quality of financial reports, including the competence of human resources, the effective use of information technology, and the strength of internal control systems. This study aims to assess the impact of human resource quality, information technology utilization, and internal control systems on the financial report quality of village administrations in Tapos District. A quantitative descriptive approach was employed, using data gathered from 100 respondents. The data were analyzed through various tests, including descriptive statistics, validity and reliability assessments, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-tests, and the coefficient of determination. The results showed that all three independent variables simultaneously affect financial report quality. These results highlight the importance of competent personnel, technology use effectiveness, and strong internal controls in producing high-quality financial information.